Context-Dependent Viral Transgenerational Immune Priming in Honey Bees (Hymenoptera: Apidae). Issue 1 (7th February 2022) - Lang, Sarah; Simone-Finstrom, Michael; Healy, Kristen
Abstract: Transgenerational immune priming is the process of increased resistance to infection in offspring due to parental pathogen exposure. Honey bees ( Apis mellifera L. (Hymenoptera: Apidae)) are hosts to multiple pathogens, and this complex immune function could help protect against overwhelming infection. Honey bees have demonstrated transgenerational immune priming for the bacterial pathogen Paenibacillus larvae ; however, evidence for viral transgenerational immune priming is lacking across insects in general. Here we test for the presence of transgenerational immune priming in honey bees with Deformed wing virus (DWV) by injecting pupae from DWV-exposed queens and measuring virus titer and immune gene expression. Our data suggest that there is evidence for viral transgenerational immune priming in honey bees, but it is highly context-dependent based on route of maternal exposure and potentially host genetics or epigenetic factors.